Background Studies of the Electric Dipole Moment Experiment at the European Spallation Source - Ripa,Alexander (2025)
The standard model can be tested by measuring the electric dipole moment of the neutron. The standard model predicts |d_n| ~ 10^{-32} ecm while experimental searches have reached a sensitivity of |d_n| < 1.8*10^{-26} ecm. Discovery of a nEDM magnitude above |d_n| ~ 10^{-32} ecm would indicate a CP-violation from beyond the standard model physics. An experiment using a novel technique to combine the production and storage of UCN to increase the statistical sensitivity was proposed at the spallation neutron source at Oak Ridge National Laboratory in the USA. This would have allowed much more precise nEDM measurements. The prospects of moving the experiment to the ESS are currently under study. The results suggest almost complete removal of cold/thermal background and indicate that the fast neutron background will be reduced significantly already in the first 15 meters of the beamline.
Keywords: ESS; neutrons; electric dipole moment; nEDM; PHITS; McStas; neutron guides; beamline; simulation